2020
DOI: 10.1186/s13058-020-01346-y
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib facilitates metastatic breast cancer spreading by inducing endothelial cell senescence

Abstract: Background Sunitinib, a receptor tyrosine kinase (RTK) inhibitor that targets multiple receptors such as vascular endothelial growth factor receptors (VEGFRs), was approved for cancer treatment in 2006. However, it was unsuccessful in treating certain cancers, particularly metastatic breast cancer (MBC), and the mechanism underlying this “sunitinib resistance” remains unclear. Herein, we investigated whether the sunitinib-associated inferior survival benefit in MBC was due to sunitinib-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
(72 reference statements)
2
23
0
1
Order By: Relevance
“…While less well established, it seems likely that other abundant stromal cells populating particular tumor microenvironments will prove to undergo senescence, and thereby modulate cancer hallmarks and consequent tumor phenotypes. For example, therapy-induced senescent tumor endothelial cells can enhance proliferation, invasion, and metastasis in breast cancer models (124,125).…”
Section: Senescent Cellsmentioning
confidence: 99%
“…While less well established, it seems likely that other abundant stromal cells populating particular tumor microenvironments will prove to undergo senescence, and thereby modulate cancer hallmarks and consequent tumor phenotypes. For example, therapy-induced senescent tumor endothelial cells can enhance proliferation, invasion, and metastasis in breast cancer models (124,125).…”
Section: Senescent Cellsmentioning
confidence: 99%
“…In particular, the production of CXCL11 from endothelial cells was shown to promote the cell proliferation, migration, and invasion of breast cancer cells in vitro [ 174 ]. Similarly, Wang et al have shown that sunitinib-induced senescence stimulates endothelial cells to secrete pro-inflammatory cytokines, thus promoting cancer metastasis and invasion [ 175 ]. In contrast with those studies, Ruscetti et al have demonstrated that the induction of senescence in PDAC cells, through the use of a combination of palbociclib and trametinib, induced vascular remodeling within the tumor, increasing its sensitivity to cytotoxic drugs and promoting T-cell infiltration [ 176 ].…”
Section: Senescence In Non-tumor Cellsmentioning
confidence: 99%
“…Several studies revealed sunitinib, a TKI, not only targets VEGFR (32) but also inhibits PDGFR (33) and FGFR (34).Sunitinib has been used to treat a variety of cancers. Similarly, studies have reported that sunitinib treatment alone can cause ECs senescence, loose ECs connections, and promote tumor cell migration through the endothelial barrier (35). Based on the above research reports, treatment with one antitumor angiogenesis drug alone have great limit effects on cancer therapy (Figure 1).…”
Section: Antitumor Angiogenesis Therapymentioning
confidence: 83%